Picturing impact of the PEDIGREA program: a case study from Indramayu, Indonesia - Wienarto, Nugroho; Kuswara, Engkus; Hakim, Arief (2005)
Over the last twelve years, FIELD Indonesia staff has been using various participatory approaches towards measuring impact of its interventions, mainly in the framework of its involvement under FAO Community Integrated Pest Management (IPM) in Asia program. Since 2002, FIELD is one of the partners in the PEDIGREA program, focusing on participatory crop and farm animal improvement. PEDIGREA is a regional program on farmer’s management of genetic resources, i.e. rice, local vegetables and poultry, which is implemented by three NGOs in Philippines, Cambodia and Indonesia, and supported by Wageningen UR, FAO, and IPGRI APO. The first attempt in 1991 (the development of three IPM Village Profiles) involved having farmers draw and discuss the benefits of participation in a Farmer Field School (FFS). Other approaches are relying on aerial planning and interactive participation techniques, iterative appraisal approaches, and socio-economic impacts. Comparing these approaches reveals that a wide scope of options for monitoring impact is available. Here we report on the results of an impact assessment method that appeared highly practical as a participatory tool: a participatory and interactive perception measuring technique for which farmers were asked to analyze the impact of the PEDIGREA program activities in their villages by making a photograph series of the project results and discussing the photographs in the community. The process distinguishes three steps: a) a three days workshop with farmer representatives from each group/village to discuss the concept of project results and impacts, to learn how to take useful photographs, and to make a work plan of objects and situations for each village to be photographed; b) a two week period of activities in each village to take photos, to select the interesting pictures, and to write the explanatory notes for each of the photos; c) a three days workshop to finalize the notes for each picture, to reflect on the program impacts and farmer’s benefits, to evaluate the impact study process, and to develop follow-up plan for each group/village. Some of the major results as visualized in the impact monitoring approach include: other farmers in the villages started to learn the breeding process from the farmer participants in the FFS; other farmers started to ask for and plant the local vegetable seeds, e.g. luffa and bitter gourd, which resulted from breeding activities in the village; better prices in local market for luffa produce by the farmer participants were realized; and some village authorities provided resources to the groups to conduct local field studies.